Early healing after treatment of coronary lesions by thin strut everolimus, or thicker strut biolimus eluting bioabsorbable polymer stents: The SORT‐OUT VIII OCT study. Issue 4 (5th February 2023) - Andreasen, Lene N.; Balleby, Ida R.; Barkholt, Trine Ø.; Hebsgaard, Lasse; Terkelsen, Christian J.; Holck, Emil N.; Jensen, Lisette O.; Maeng, Michael; Dijkstra, Jouke; Antonsen, Lisbeth; Kristensen, Steen D.; Tu, Shengxian; et al.
Abstract: Aims: Early healing after drug‐eluting stent (DES) implantation may reduce the risk of stent thrombosis. The aim of this study was to compare patterns of early healing after implantation of the thin strut everolimus‐eluting Synergy DES (Boston Scientific) or the biolimus‐eluting Biomatix Neoflex DES (Biosensors). Methods and Results: A total of 160 patients with the chronic or acute coronary syndrome were randomized 1:1 to Synergy or Biomatrix DES. Optical coherence tomography (OCT) was performed at baseline and at either 1‐ or 3‐month follow‐up. The primary endpoint was a coronary stent healing index (CSHI), a weighted index of strut coverage, neointimal hyperplasia, malapposition, and extrastent lumen. A total of 133 cases had OCT follow‐up and 119 qualified for matched OCT analysis. The median CSHI score did neither differ significantly between the groups at 1 month: Synergy 8.0 (interquartile range [IQR]: 3.0; 14.0) versus Biomatrix 8.5 (IQR: 4.0; 15.0) ( p  = 0.47) nor at 3 months: Synergy 6.5 (IQR: 2.0; 13.0) versus Biomatrix 6.0 (IQR: 4.0; 11.0) ( p  = 0.83). Strut coverage was 84.6% (IQR: 72.0; 97.9) for Synergy versus 77.6% (IQR: 70.1; 90.3) for Biomatrix ( p  = 0.15) at 1 month and 90.3% (IQR 79.0; 98.8) (Synergy) versus 83.9% (IQR: 77.5; 92.6) (Biomatrix) ( p  = 0.068) at 3 months. Pooled 1 ‐ and 3‐month coverage was 88.6% (IQR: 74.4; 98.4) for Synergy compared with 80.7% (IQR: 73.2; 90.8) for Biomatrix ( p  = 0.02). Conclusions: The early healing response after treatment with the Synergy or Biomatrix DES did not differ significantly as determined by a healing index. The Synergy DES showed overall better early stent strut coverage.